Universal screening for intimate partner and sexual violence in trauma patients: An EAST multicenter trial. Issue 1 (July 2017) - Zakrison, Tanya L.; Ruiz, Xiomara; Gelbard, Rondi; Cline, John; Turay, David; Luo-Owen, Xian; Namias, Nicholas; Crandall, Marie; George, Jessica; Williams, Brian H.
Abstract : BACKGROUND: A single-center trial recently demonstrated a prevalence of 14% of intimate partner and sexual violence (IPSV) among both male and female trauma patients, regardless of mechanism of injury. We aimed to determine if this phenomenon was similar to rates in other trauma centers by assessing the feasibility of universal screening and determining the prevalence and association of IPSV with other trauma-associated comorbidities. METHODS: We designed an Eastern Association for the Surgery of Trauma–supported multicenter, prospective observational cohort study involving four Level I trauma centers throughout the United States. Screening occurred from March 2015 to April 2016. We performed universal screening of adult trauma patients using the validated HITS (Hurt, Insult, Threaten, Scream) and SAVE (sexual violence) screening surveys. Trauma recidivism, substance use, and mental illness were also measured and were classified as "trauma-associated comorbidities." Chi-squared test compared categorical variables with significance at p <0.05. Parametric data is presented as mean ± standard deviation. RESULTS: A total of 2, 034 eligible trauma patients were screened by clinical social workers at each site over 1 year. The mean age was 37.05 ± 20.32 with 63% men, 37% women, and one transgendered participant. The overall rate of IPSV was 11.4%. The proportion of positive screens for men was 9.3%, with variability between centers (3.8–72.7%), and for women was 16.1% (15.3–50.0%) ( p < 0.001). The transgendered patient screened positive for IPSV. Of patients who screened positive for IPSV, 60.0% had one or more trauma-associated comorbidity compared to 15.1% of patients who screened negative ( p < 0.001). CONCLUSION: More than one in nine trauma patients is at risk of IPSV, regardless of gender or mechanism of injury. IPSV may be a risk factor for other trauma-associated comorbidities. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, level II; Care Management, level III.